Development and Validation of Higher Order Thinking Skills Based Instrument on Reaction Rate Subject - Nevia Pradani; Suharti Suharti; Hayuni Retno Widarti (JPP (Jurnal Pendidikan dan Pembelajaran), 2021)
This development aims to produce a product in the form of a HOTS-based instrument on the reaction rate subject. The development model used refers to the ADDIE development model carried out in three stages: analysis, design, and development. The developed question instruments were validated by the expert validator and then ran a small-scale test. Data analysis obtained value validation of instruments at 93.33% and included very good criteria. The 15 items developed were declared valid and reliable with the Cronbach's Alpha value equal to 0.805. As much as 10 items are classified as moderate, 1 item is classified as easy, and 4 items are classified as difficult and 3 items out of 15 items have an ineffective distracting effect. Based on these results, it can be concluded that the question instrument is suitable for use.